DIFFERENT APPROACHES IN ANALYZING CHYMOSIN PURITY - Nestorovski, T.; Velkoska–Markovska, L.; Srbinovska, S.; Miskoska –Milevska, E.; Petanovska –Ilievska, B.; Popovski, Z.T. (University Ss. Cyril and Methodius in Skopje, 2019)
Chymosin is a specific proteolytic enzyme found in rennet, and is the key enzyme in cheese production classified in the aspartic endopeptidases (EC 3.4.23.4). The aim of this study was to determine the purity of different commercially available chymosins and its equivalents using electrophoretic and chromatographic techniques. Chymosins produced by the company Chr. Hansen, CHY-MAX 200 and CHY-MAX Plus, CHY-MAX PowderExtra NB, as well as Maxiren 1800 Granulate from the company DSM, Sirnik from SZR – Travnik, Kraljevo and Planika from Mikroprocessing, Bileca were used as materials for this study. The purity level of the commercially available enzymes was analyzed using electrophoretic (sodium dodecyl sulfate polyacrylamide gel electrophoresis or SDS-PAGE) and chromatographic (Rapid Resolution Liquid Chromatography or RRLC) techniques. Results showed no presence of undeclared protein fractions due to inappropriate purification process in the samples except for CHY-MAX М 200 which had two protein fractions, most likely as a result of a polymorphism. All the CHY-MAX and Maxiren samples have chymosin as the active component (36 kDa), except for Planika and Sirnik which have a natural protease from R. miehei. Chromatographic analysis showed that beside the active component (chymosin), the preservative sodium benzoate was present in varying concentrations in all but CHY-MAX PowderExtra NB.
Keywords: chymosin, purity, chromatography, electrophoresis